2023
DOI: 10.1039/d3ra00016h
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of waste banana peels as heterogeneous catalysts in room-temperature biodiesel production using a homogenizer

Abstract: Banana peels as agro-waste residues contain potassium oxide as the main component after calcination. The calcined waste banana peels (WBPs) successfully transesterified palm oil to biodiesel at room temperature using a homogenizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The GC analysis was performed following the EN 14103:2011 standard. 20,27 The conversion of 97.1 ± 0.7% was determined using GC analysis which was quite similar to the conversion determined based on acid value. Further, the biodiesel formation was confirmed using a spectrophotometer FT-IR.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…The GC analysis was performed following the EN 14103:2011 standard. 20,27 The conversion of 97.1 ± 0.7% was determined using GC analysis which was quite similar to the conversion determined based on acid value. Further, the biodiesel formation was confirmed using a spectrophotometer FT-IR.…”
Section: Resultssupporting
confidence: 66%
“…The catalyst plays a crucial role in the esterification reaction as it can accelerate the reaction rate. 20 Catalyst concentration has a linear relation with the biodiesel conversion. It has been reported that increasing catalyst concentration could increase biodiesel conversion until reaches the maximum point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of potassium, phosphate, and silicon (Si−O−Si) stretching vibrations in the BBB may be related to the low-intensity peak at 700−960 cm −1 . 27 The ambient CO 2 adsorption onto metal oxides found in the activated biomass catalyst can be attributed to the peak at 1173 cm −1 . 52 The FTIR analyses of the UBB and BBB materials demonstrated that variations in the peak intensity and shift substantiated the structural changes that occurred during the calcination and activation processes.…”
Section: Characterization Of the Koh-assisted Banana Bunch Stalkmentioning
confidence: 98%